2014
DOI: 10.1063/1.4871856
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bifurcation dynamics of turbulent transport models for the L-H transition

Abstract: In more than three decades, a large amount of models and mechanisms have been proposed to describe a very beneficial feature of magnetically confined fusion plasmas: the L-H transition. Bifurcation theory can be used to compare these different models based on their dynamical transition structure. In this paper, we employ bifurcation theory to distinguish two fundamentally different descriptions of the interaction between turbulence levels and sheared flows. The analytic bifurcation analysis characterises the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…[6] In order to study the nonlinear mechanism associated with the LH transition, lots of theoretical and experimental efforts have been made, which revealed that the zonal flows play a key role in the drift wave turbulence, [6,7] mean 𝐸 × 𝐵 flow will suppress the turbulence, [8,9] and different types of transitions (such as oscillating, sharp and smooth ones) are also discovered. [10,11] The active studies in this field are aimed at an understanding of nonlinear physics processes in coherent structure formation and anomalous transport in plasmas. [12] The importance of zonal flows in the LH transition was experimentally demonstrated through bicoherence analysis on DIII-D experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In order to study the nonlinear mechanism associated with the LH transition, lots of theoretical and experimental efforts have been made, which revealed that the zonal flows play a key role in the drift wave turbulence, [6,7] mean 𝐸 × 𝐵 flow will suppress the turbulence, [8,9] and different types of transitions (such as oscillating, sharp and smooth ones) are also discovered. [10,11] The active studies in this field are aimed at an understanding of nonlinear physics processes in coherent structure formation and anomalous transport in plasmas. [12] The importance of zonal flows in the LH transition was experimentally demonstrated through bicoherence analysis on DIII-D experimental data.…”
Section: Introductionmentioning
confidence: 99%